2004
DOI: 10.1097/01.prs.0000105632.86651.ef
|View full text |Cite
|
Sign up to set email alerts
|

Reepithelialization of a Full-Thickness Burn from Stem Cells of Hair Follicles Micrografted into a Tissue-Engineered Dermal Template (Integra)

Abstract: We report a head and neck full-thickness burn injury that was reconstructed with a tissue-engineered dermal template and then early implantation of microdissected hair follicles through the silicone epidermis 12 days after the burn injury. The treatment resulted in complete reepithelialization and a hair-bearing scalp without the need for a split-thickness skin graft. Restoration of the stem cell population, hair growth, and earlier reepithelialization were achieved using this novel micrografting technique, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(52 citation statements)
references
References 8 publications
2
48
0
2
Order By: Relevance
“…Several studies have unambiguously identified the hair follicle as a major reserve of adult stem cells (15,16). Dermal grafts from the scalp (10), early implantation of microdissected hair follicles through a silicone epidermis (11) and hair grafting (17) are used for cutaneous wound repair; however, the procedures are complicated. In the present study, hair follicles without epidermal or interfollicular tissue were transplanted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have unambiguously identified the hair follicle as a major reserve of adult stem cells (15,16). Dermal grafts from the scalp (10), early implantation of microdissected hair follicles through a silicone epidermis (11) and hair grafting (17) are used for cutaneous wound repair; however, the procedures are complicated. In the present study, hair follicles without epidermal or interfollicular tissue were transplanted.…”
Section: Discussionmentioning
confidence: 99%
“…The scalp has been identified as an excellent donor site for thin skin grafts (9); however, the scalp dermal graft presents a limited surface area and is <3-4% of the total body surface area (10). Clinical and histological evidence has shown that the rapid healing of the scalp dermal graft is attributed to the differential potential of the cells in the hair follicles, and that re-epithelialization can also occur from grafted hair follicles (11). Numerous types of cells with multiple differentiation potentials have been identified in hair follicles, and their relative contribution to re-epithelialization has been recently determined (12).…”
Section: Introductionmentioning
confidence: 99%
“…Human ectodermal stem cells from micro-grafted hair follicles have been used clinically to repopulate a dermal template for burned skin replacement. 37 Another example of ectodermal stem cell engineering is rat neural stem and progenitor cells differentiating into functional neuronal circuits in a 3D collagen gel, with the potential to repair injury to the central nervous system. 38 Endodermal stem cells differentiate into many of the internal organs, such as the liver, lung, and pancreas, and have been used, for example, to generate b-like cell colonies that increase insulin secretion in response to glucose.…”
Section: Tissue Locationmentioning
confidence: 99%
“…Existen informes de casos de reconstrucción de cuero cabelludo con Integra® y luego implantes a base de microdisecciones de folículos pilosos a través de la lámina de silicona, resultando una reepitelización completa y un cuero cabelludo con cabello sin necesidad de un injerto de piel parcial. Se logró de esta manera la restauración de la población de células troncales, crecimiento del cabello y reepitelización temprana a través de esta nueva técnica de microinjertos (12).…”
Section: Discussionunclassified